A minőség biztosításának kihívásai a magyar felsőoktatásban - Surman, Vivien; Szabó, Tibor (Vezetéstudomány / Budapest Management Review, 2020)
Hungarian higher education institutions are primarily characterized by state-coordinated culture. The legislation focuses on the quality-related procedures and responsibilities, and based on the authors’ document analyses, they concluded that direct ministry intervention is a widely used tool and the concept of quality is linked to the quality perception of the Ministry. The quality management documentation system of the Budapest University of Technology and Economics includes parts from every group of Clark’s typology. The key element of the documentation system is the TQM philosophy, and examining the university’s quality management system according to that, related to customer focus, most of the stakeholders’ opinions are monitored. Currently, this system includes four parts: concentrating on the graduates, the enrolled students, the BME Job Fair Exhibitors and the secondary school students attending the University’s Open Day. The continuous assessment of stakeholders’ opinions and analysis of results could provide a basis for educational development programs.